A new methodology for facilitating the design of safety-related parts of control systems in machines according to ISO 13849:2006 standard. (June 2018) - Porras-Vázquez, Alberto; Romero-Pérez, Julio-Ariel
Highlights: SRP/CS in machinery are mostly designed according to ISO 13849-1:2006. The design method in this ISO standard is based on a trial-and-error procedure. The result could be far from the optimal solution in terms of cost and safety. A new method for designing SRP/CS according to ISO 13849-1:2006 is presented. The proposed method, implemented in a software, reduces time and cost investment. Abstract: Safety is a fundamental requirement of production systems considered throughout all the stages of a machine's lifecycle. Due to its importance to avoid accidents and injuries, safety specifications have been explicitly regulated by legislation over decades. Nowadays, safety functions of machinery are increasingly designed and validated according to ISO 13849-1:2006. This standard replaced the previous EN 954-1:1997 standard (withdrawn on December 31st, 2001) and introduced new concepts to adapt the designs to more demanding safety requirements. The workflow stated in ISO 13849-1:2006 for designing safety-related parts of control systems (SRP/CS) is based on a trial-and-error procedure whose result could be far from an optimal solution in terms of trade-off between economic cost and safety capabilities. Furthermore, this approach increases the time needed for selecting adequate SRP/CS components. In this paper, we present a new methodology for designing SRP/CS according to ISO 13849-1:2006. Our proposal reconceives the current design process in order to offer novel guidelines to reduce both time and cost investment. The theoretical ideas examined here have been implemented in a new software tool which has been evaluated through two practical cases, the results of which are discussed in the paper.